A Prospective Study of Lipid Profile and BMI as Risk Factors in MI in Young [ (Academia Journal of Medicine, 2019)
Background: In recent years’ cardiovascular disease is the leading cause of mortality and morbidity worldwide in both male and female is  accepted. The urbanisation has made its impact on the rising incidence of MI in India. One should not overlook however that MI in rural areas  has doubled as well. This study is aimed at studying the Dyslipidaemia and Body mass index as risk factors in MI in young in rural  background. Subjects and Methods: This prospective observational study was done in General Medicine Department at SVS hospital during  July 2007 to July 2009.Out of 100 patients admitted with MI 20 selected and studied based on inclusion and exclusion criteria. Results: The  study showed patients with high LDL>100mg/dl and low HDL30 had increased risk for MI than otherwise. It was also observed that female preponderance was more compared to males. Conclusion: The study shows that dyslipidaemia and abnormal BMI do contribute to MI in young in rural background.
Keywords: Body mass index; dyslipidaemia; high density lipoproteins; low density lipoproteins; Myocardial infarction